2010
DOI: 10.1186/1476-511x-9-86
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the apolipoprotein C-III 3238C>G polymorphism and alcohol consumption on serum triglyceride levels

Abstract: Background Both apolipoprotein (Apo) C-III gene polymorphism and alcohol consumption have been associated with increased serum triglyceride (TG) levels, but their interactions on serum TG levels are not well known. The present study was undertaken to detect the interactions of the ApoC-III 3238C>G (rs5128) polymorphism and alcohol consumption on serum TG levels. Methods A total of 516 unrelated nondrinkers and 514 drinkers aged 15-89 were randomly selected from our prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 73 publications
3
34
0
Order By: Relevance
“…Our findings showed that lowering of cholesterol levels by ALC+AVS concomitantly prevented cell invasion in the vasculature, thereby minimizing the early event of atherosclerosis. This was supported by reduction of serum cholesterol levels, cholesterol build-up in different size of the vessels, thickening of arterial/capillary walls, and intracranial blood pressure in alcohol consumptionfollowing ALC/Lipitor ® administration.The increase in serum LDL cholesterol levels associated with alcohol diet ingested animals in this study is similar to serum LDL cholesterol levels observed in human alcoholics[31,32]. …”
Section: Discussionsupporting
confidence: 85%
“…Our findings showed that lowering of cholesterol levels by ALC+AVS concomitantly prevented cell invasion in the vasculature, thereby minimizing the early event of atherosclerosis. This was supported by reduction of serum cholesterol levels, cholesterol build-up in different size of the vessels, thickening of arterial/capillary walls, and intracranial blood pressure in alcohol consumptionfollowing ALC/Lipitor ® administration.The increase in serum LDL cholesterol levels associated with alcohol diet ingested animals in this study is similar to serum LDL cholesterol levels observed in human alcoholics[31,32]. …”
Section: Discussionsupporting
confidence: 85%
“…On ordinary days, they are vegetarians [7][8][9]. Third, it is clearly established that serum lipid levels are regulated by multiple environmental and genetic factors, and their interactions [7][8][9][10][11][12]. Although we have detected the interactions of 10 SNPs and high BMI on serum lipid levels in this study, there are still many unmeasured environmental and genetic factors and their interactions.…”
Section: Discussionmentioning
confidence: 62%
“…Genomic DNA was extracted from the peripheral blood leukocytes by the phenol-chloroform method [10][11][12]. Genotyping of rs2066715, rs1044925, low-density lipoprotein receptor (LDL-R) Avak, rs2070895, rs2000813, rs1801133, rs3757354, rs505151, rs2016520, and rs5888 was performed using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP).…”
Section: Genetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous single nucleotide polymorphisms (SNPs) and alcohol consumption have been associated with lipid metabolism and variation in serum lipid profiles. The interactions between several SNPs and alcohol consumption on serum lipid levels and CAD (Corella et al., ; Jensen et al., ; Liu et al., ; Ruixing et al., ; Yin et al., ) have also been reported previously.…”
mentioning
confidence: 53%